Distribution of nerve fibers in the optic nerve of the quail: a laser-degeneration study - Carri, Néstor (1980)
Normal visual function requires specific connections between the retina and the visual centers. Connections arise after migration of the optic axons to the brain; however, the biological basis of their specificity are mostly unknown. Som9 of the postulated mechanisms require a recognition between axons and brain neurons, whereas others depend on the maintenance of a retinotopic order along the optic pathways. (Párrafo extraído a modo de resumen)